SYNTHESIS OF NEW BLOCK COPOLYMERS BASED ON POLYETHYLENGLYCOL AND 2-OXAZOLINES - Rueda, Juan (2015)
New block copolymers (typ AB) were obtained by the ring opening cationic polymerization of2-cyclopropyl- and 2-methoxycarbonylethyl-2-oxazoline, using tosylated polyethylenglycolas initiator. In block copolymers, the polymerization grade of polyethylenglycol (PEG)segment was always 45 units and of the poly(2-oxazolines) segment was variable, between33 to 242 units. The block copolymers, containing 2-methoxycarbonylethyl-2-oxazoline,were submitted to a quantitative hydrólisis of ester groups to obtain carboxylic acid units.The copolymers were characterized structurally by nuclear magnetic resonance spectroscopyand they show a conformational transition (LCST) between 24 and 48°C, which was functionof the polymer structure, of its content of cyclopropyloxazoline and carboxilic acid groups.